Synthesis, protonation behavior, conformational analysis, and regioselective enzymatic acylation of the novel diamino analogue of (E)-5-(2-bromovinyl)-2'-deoxyuridine (BVDU) - Lavandera, Iván; Fernández, Susana; Ferrero, Miguel; De Clercq, Erik; Gotor, Vicente (2003)
(E)-3',5'-Diamino-5-(2-bromovinyl)-2',3',5'-trideoxyuridine (5), the diamino analogue of BVDU (1), was synthesized from BVDU. The protonation behavior of 5 has been studied by means of pH-metric measurements and NMR spectroscopy. This study allows the determination of the basicity constants and the stepwise protonation sites. Thus, the main species at physiological pH is the monoprotonated form. The conformational analysis of this nucleoside analogue was also carried out through 1H NMR spectroscopy. In addition, a convenient synthesis of N-3' and N-5' acylated derivatives was developed by regioselective enzymatic acylation. Thus, Candida antarctica lipase B (CAL-B) selectively acylated the 5'-amino group, thus furnishing nucleosides 8. On the other hand, immobilized Pseudomonas cepacia lipase (PSL-C) exhibited the opposite selectivity, conferring acylation at the 3'-amino group, thus affording derivatives 9. status: published